Qualitative Factors in Patients Who Die Shortly After Emergency Department Discharge. (15th August 2013) - Gabayan, Gelareh Z.; Sun, Benjamin C.; Asch, Steven M.; Timmermans, Stefan; Sarkisian, Catherine; Yiu, Sau; Lancaster, Elizabeth M.; Trudy Poon, K.; Kellermann, Arthur L.; Ryan, Gery; Miniel, Nicholas J.; Flansbaum, Drew; et al.
Abstract Objectives Early death after emergency department (ED) discharge may signal opportunities to improve care. Prior studies are limited by incomplete mortality ascertainment and lack of clinically important information in administrative data. The goal in this hypothesis‐generating study was to identify patient and process of care themes that may provide possible explanations for early postdischarge mortality. Methods This was a qualitative analysis of medical records of adult patients who visited the ED of any of six hospitals in an integrated health system (Kaiser Permanente Southern California [KPSC]) and died within 7 days of discharge in 2007 and 2008. Nonmembers, visits to non–health plan hospitals, patients receiving or referred to hospice care, and patients with do not attempt resuscitation or do not intubate orders (DNAR/DNI) were excluded. Under the guidance of two qualitative research scientists, a team of three emergency physicians used grounded theory techniques to identify patient clinical presentations and processes of care that serve as potential explanations for poor outcome after discharge. Results The source population consisted of a total of 290, 092 members with 446, 120 discharges from six KPSC EDs in 2007 and 2008. A total of 203 deaths occurred within 7 days of ED discharge (0.05%). Sixty‐one randomly chosen cases were reviewed. Patient‐level themes that emerged included an unexplained persistent acute change in mental status, recent fall, abnormal vital signs, ill‐appearing presentation, malfunctioning indwelling device, and presenting symptoms remaining at discharge. Process‐of‐care factors included a discrepancy in history of present illness, incomplete physical examination, and change of discharge plan by a third party, such as a consulting or admitting physician. Conclusions In this hypothesis‐generating study, qualitative research techniques were used to identify clinical and process‐of‐care factors in patients who died within days after discharge from an ED. These potential predictors will be formally tested in a future quantitative study.